Studi tentang Faktor-Faktor Penentu Customer Loyalty pada Grabfood: Investigasi atas Perceived Value, Customer Satisfaction, dan Switching Cost - Anna Rosaria Firdhiani; Ari Setiyaningrum (Ekonomi Bisnis, 2020)
This research was conducted to test the determining factors of customer loyalty on Grabfood which include perceived value, customer satisfaction and switching cost. This research also tests the mediating role of customer satisfaction on the influence of perceived value on customer loyalty and tests the moderation role of switching cost on the influence of customer satisfaction on customer loyalty. The sampling method in this study is non-probability sampling through purposive sampling technique. The survey was conducted by distributing questionnaires to 160 respondents who had used the Grabfood application at least 3 times. The data is analyzed using macro process SPSS moderation mediation analysis. The results showed that perceived value and customer satisfaction affect customer loyalty, perceived value affects customer satisfaction, customer satisfaction mediates perceived value influence on customer loyalty, and switching cost does not moderate the influence of customer satisfaction on customer loyalty.